1981
DOI: 10.1084/jem.154.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Virus-specific interferon action. Protection of newborn Mx carriers against lethal infection with influenza virus.

Abstract: The efficacy of interferon in antiviral protection of newborn mice differing at the Mx locus was investigated. Adult mice bearing the allele Mx exhibit a high degree of specific resistance toward lethal challenge with influenza viruses. In contrast, newborn Mx carriers are virtually as susceptible to influenza viruses as newborn mice devoid of Mx. Resistance can be abrogated by treating adult animals with anti-interferon serum. Here, we provide direct evidence of a virus-specific effect of interferon in vivo: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 17 publications
4
40
0
Order By: Relevance
“…Haller et al demonstrated that in the presence of IFN, mice with a functional Mx1 gene, the murine homologue of the human MxA gene, were more likely to survive a lethal influenza virus challenge than mice without a functional Mx1 gene (3). IFN-␣ is required to induce the Mx1-mediated influenza virus resistance, because treatment of mice with an anti-IFN Ab eliminates the beneficial effect of the intact Mx1 gene (3,24,25). However, the role of IFN-induced MxA in controlling influenza virus replication in humans and other animals is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Haller et al demonstrated that in the presence of IFN, mice with a functional Mx1 gene, the murine homologue of the human MxA gene, were more likely to survive a lethal influenza virus challenge than mice without a functional Mx1 gene (3). IFN-␣ is required to induce the Mx1-mediated influenza virus resistance, because treatment of mice with an anti-IFN Ab eliminates the beneficial effect of the intact Mx1 gene (3,24,25). However, the role of IFN-induced MxA in controlling influenza virus replication in humans and other animals is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of IFN-␣␤ occurs after TLRs, the retinoic acidinducible gene I (RIG-I), or the melanoma differentiation-associated gene 5 (MDA-5) bind dsRNA or ssRNA, leading to the activation of IFN-regulatory factors 3 and 7 (IRF-3 and IRF-7), NF-B, and AP-1 (35)(36)(37). Secreted IFN-␣␤ binding to the IFN-␣ receptor activates ISG factor 3 (ISGF3), which binds the ISRE (3,24,35). ISGF3 binding to ISRE activates the transcription of MxA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe the 2C12-cross-reacting protein most likely is the human homolog of protein Mx (3,4,13). The significance of the homologous human protein for host defense of humans against influenza viruses is less clear and remains to be investigated.…”
mentioning
confidence: 99%